2017
DOI: 10.1111/jocn.14109
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ perspectives on how an e‐message system supports cross‐sectoral communication in relation to medication administration: A qualitative study

Abstract: E-message systems must meet home care nurses' need for information to ensure that safe medication administration does not depend on the knowledge of the individual nurse. Moreover, other system factors that influence interprofessional collaboration and nurses' cross-sectoral communication must be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 50 publications
2
44
0
Order By: Relevance
“…Several recent studies have focused on lack of information in relation to medication administration (e.g. Foged et al, 2018;Kollerup et al, 2018;Patterson et al, 2019).These studies concluded that reducing medication discrepancies in the transition from hospital to home requires improved communication, through access to electronic medical records or standardised transfer forms. Our findings show that providing accurate medication management is not only simply a matter of safe transition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have focused on lack of information in relation to medication administration (e.g. Foged et al, 2018;Kollerup et al, 2018;Patterson et al, 2019).These studies concluded that reducing medication discrepancies in the transition from hospital to home requires improved communication, through access to electronic medical records or standardised transfer forms. Our findings show that providing accurate medication management is not only simply a matter of safe transition.…”
Section: Discussionmentioning
confidence: 99%
“…Further, research has stressed that the use of different information and communication technology across sectors does not support the necessary exchange of information (Melby et al, 2015;Foged et al, 2018). Deficits in communication and a lack of coordination in the discharge process can cause serious breakdowns in the continuity of care.…”
mentioning
confidence: 99%
“…Details on the participants are shown in Table . More details on the data collection, relations with the participants and the authors have previously been reported (Foged et al, ; Petersen et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The e‐message system held five key elements, including reports and notifications related to admission and discharge as well as care plans and a message platform. More details on the system have been reported previously (Foged et al, ; Petersen et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation